A Kriging framework for the efficient exploitation of the nanoscale junctioless DG MOSFETs including source/drain extensions and hot carrier effect, ISSN / e-ISSN 1369-7021 / 1873-4103 - Toufik, Bentrcia; DJEFFAL Fayçal; Elasaad, Chebaki; Djemai, Arar (materials-todaymaterials-today, 2017)
Recently, the Junctionless Double Gate MOSFET with source/drain extensions has proved competitive performance measures due to the reduction of the series resistance between the metal contacts and source/drain regions. However, the precise modeling of different response functions is still an important issue especially at nanoscale level because of the inclusion of complex phenomena such as quantum transport mechanisms and hot carrier degradation effect. In this perspective, our aim in the presented work is to investigate the efficiency of a novel approach based on Kriging metamodeling and multi-objective particle swarm optimization for the exploitation of the considered device in terms of some analog/RF performances. Data generated by ATLAS-2D simulator, are used to establish Kriging metamodels for the Gain and Transconductance Generation Factor. It is highlighted that the obtained models can be used accurately in a multi-objective context to offer several Pareto optimal configurations. As a result, a wide range of biasing configurations is available to the designer depending on imposed constraints.